Synthesis and characterization of bioplastics made from chitosan combined using glycerol plasticizer - Hasri Hasri; Muhammad Syahrir; Diana Eka Pratiwi (Indonesian Journal of Fundamental Sciences, 2021)
Utilization of taro tuber starch bioplastic as an alternative solution to reduce environmental pollution due to synthetic plastic waste is non-toxic if contaminated with food and environmentally friendly because it can be decomposed by microorganisms. This study aims to determine the bioplastic characteristics of taro tuber starch with the addition of glycerol and chitosan plasticizers. Characterization of bioplastics through biodegradation, water resistance, elongation, and functional group analysis using FTIR. The results of the study of bioplastics with glycerol plasticizers have thickness values in the range of 0.10 mm – 0.20 mm, water resistance values in the range of 15.09% - 66.04%, tensile strength values in the range of 6.9939 MPa – 9.4746 MPa, elongation values. in the range of 4.99% - 8.47%, biodegradation in the range of 48.30% for 12 days. The resulting bioplastic has a thickness value in the range of 0.10 mm to 0.20 mm based on JIS standards, the thickness value of taro starch bioplastic has met the standard and the tensile strength value of the sorbitol plasticizer has met SNI